Improve Mathematics Learning Outcomes in High School with Critical Thinking Skills through Independence Problem-Based Learning (IPBL) Approach - Wardana, Ali (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2023)
Education at the High School level (SMA) plays a crucial role in shaping students' critical thinking, which is an essential skill for success in both the educational and everyday life contexts. This research investigates how students' critical thinking skills can be enhanced through the implementation of the Independence Problem-Based Learning (IPBL) Mathematics Learning Approach in the high school environment. This study explains the concept of critical thinking, the importance of critical thinking in education, and the framework of Independence Problem-Based Learning (IPBL). The research methodology includes research design, population, sample, research instruments, and the process of IPBL implementation. The research findings reveal changes in students' critical thinking abilities after participating in IPBL learning and measure students' perceptions of this approach. In the discussion, this research evaluates the impact of IPBL-based Mathematics learning on students' critical thinking abilities, analyzes the factors influencing the success of IPBL, and highlights the implications of these research findings in the context of improving education at the high school level. The results of this research provide a better understanding of the potential of Independence Problem-Based Learning (IPBL) Mathematics Learning to enhance learning outcomes in high school and promote the development of mathematics teaching methods focused on improving students' critical thinking skills.